Pemanfaatan Informasi Dan Teknologi Dalam Implementasi Manajemen Pengendalian Risiko Likuiditas Di Bmt Ugt Nusantara - Sholeh Wafie; Segaf Segaf (ITB AAS INDONESIA Surakarta, 2023)
Some of the common issues and constraints faced by sharia cooperatives today concern the management of risk management, including liquidity risk. This risk is prone to occur in many sharia cooperatives, the majority is due to the simplicity of the information and technology (IT) systems they have. As a result, a commotion arose from the members because they had lost trust because the Cooperative could not fulfill its obligations to members when withdrawing their deposits. This is due to weak liquidity, and a weak supervisory and control system from managers regarding liquidity needs and time deposits or general term savings that are due. In fact, this function can be replaced by an increase in the latest Information and Technology systems. The use of technology has a very significant role in controlling liquidity risk. This study analyzes the use of information and technology in managing liquidity risk control in the BMT UGT Nusantara Cooperative. The methodological approach used is descriptive qualitative analysis. The results of the study show that the improvement of information and technology systems has a very important role in anticipating the occurrence of liquidity weaknesses.